In Vitro Screening of Fungicides and Plant Extracts Against Pathogenic Fungi Associated With Infected Fruits of Carica Papaya L (Journal of Bangladesh Academy of Sciences, 2018)
Five fungicides viz., Autostin 50 WDG, Dithane M 45, Greengel 72 WP, Ridomil Gold MZ 68 WG   and Tilt 250 EC exclusively were tested against three pathogenic fungi viz., Colletotrichum gloeosporioides (Penz.) Sacc., Fusarium nivale (Fr.) Ces. and Fusarium sp. associated with Carica papaya L. following poisoned food technique. At 100 ppm  Autostin showed complete growth inhibition of C. gloeosporioides, F. nivale and Fusarium sp., while  Tilt 250 EC showed complete growth inhibition of C. gloeosporioides at the same concentration. These fungicides at 400 and 500 ppm showed complete growth inhibition of F. nivale. Tilt 250 EC showed complete growth inhibition of Fusarium sp. at 300, 400 and 500 ppm. Eight plants extract, viz., Adhatoda vasica, Azadirachta indica, Curcuma longa, Ocimum sanctum, Lantana camara, Tagetes erecta, Thuja orientalis and Vitex negundo were also tested for their  efficacy at 5, 10, 15 and 20% concentrations against these pathogenic fungi. Out of the eight plant extracts, Ocimum sanctum showed highest (88.57%) radial growth inhibition of C. gloeosporioides at 20% concentration. Curcuma longa showed highest (88.55%) radial growth inhibition of F. nivale and Adhatoda vesica showed highest (80.02%) radial growth inhibition of Fusarium sp. at the same concentrations. The present investigation suggests Autostin 50 WDG and Tilt 250 EC as best inhibiting chemical fungicides for C. gloeosporioides, F. nivale and Fusarium sp. Extracts of O. sanctum, C. longa and Adhatoda vesica were found to be superior to other plant extracts tested.Journal of Bangladesh Academy of Sciences, Vol. 42, No. 2, 121-128, 2018